A Discovery of a Genetic Mutation Causing Reduction of Atrogin-1 Expression in Broiler Chicken Muscle - Li, Jinxiu; Hu, Yiqing; Li, Li; Wang, Yuzhe; Li, Qinghe; Feng, Chungang; Lan, He; Gu, Xiaorong; Zhao, Yiqiang; Larsson, Mårten; Hu, Xiaoxiang; Li, Ning (Frontiers in Genetics, 2019)
Chickens are bred all over the world and have significant economic value as one of the major agricultural animals. The growth rate of commercial broiler chickens is several times higher than its Red Jungle fowl (RJF) ancestor. To further improve the meat production of commercial chickens, it is quite important to decipher the genetic mechanism of chicken growth traits. In this study, we found that broiler chickens exhibited lower levels of E3 ubiquitin ligase muscle atrophy F-box (MAFbx or Atrogin-1) relative to its RJF ancestor. As a ubiquitin ligase, Atrogin-1 plays a crucial role in muscle development in which its up-regulation often indicates the activation of muscle atrophic pathways. Here, we showed that the Atrogin-1 expression variance partly affects chicken muscle growth rates among different breeds. Furthermore, we demonstrated that the reduced expression of Atrogin-1 in broiler chickens was ascribed to a single nucleotide polymorphism (SNP), which inhibited the binding of transcription regulators and attenuated the enhancer activity. The decreased Atrogin-1 in broiler chickens suppresses the catabolism of muscle protein and preserves muscle mass. Our study facilitates the understanding of the molecular mechanism of chicken muscle development and has a high translational impact in chicken breeding.